Food Label Usage and Understanding Among Singaporeans - Ameen Talib; Jocelyn Sebastian Pereira (Indonesian Journal of Multidisciplinary Science, 2023)
This study examines if the demographic characteristics influencing the usage of food labels and the extent to which Singaporeans read, understand and interpret food labels. Results suggest that food label reading prevalence in Singapore is high, with fat calories and sugar being read more often than other types of food label items. Healthier Choice Symbol is the most read label format in Singapore. Females are more likely to read food labels. The study also shows that, while Singaporeans positively perceived their ability to read food labels accurately, there are gaps in their perceived ability and the actual correct understanding and interpretation of food labels. The research concludes with suggestions for bridging the perceptional gaps and improving the existing food label formats.